(untitled) (Indian Journal of Child Health, 2021)
Tandem mass spectrometry (TMS) -based screening for homocystinuria in the routine newborn screening (NBS) primarily relies on the elevated levels of methionine (Met) in the dried blood spot (DBS) of affected neonates. However, due to the lack of required specificity of Met as a marker for homocystinuria, an additional re-sampling and follow-up analytical testing for a definitive diagnosis, emphasis us to develop second-tier testing for a more specific marker, that is homocysteine (HCY) in the same residual blood spot without any new sample. Objective: The objective of the study was to develop a novel approach for the second-tier estimation of total HCY in residual blood spot using TMS. Materials and Methods: Retrospective analysis of DBS from all neonates with deranged levels of Met and Met to phenylalanine in primary NBS was included in the study. The study duration was for a period of 24 months (November 2015-October 2017). Heel prick samples were collected within 24–72 h of birth and after the first feed. Further, the samples with abnormal Met was analyzed for total HCY by isotopic dilution approach using multiple reaction monitoring modes for mass transition m/z 136?90 for HCY, m/z 140?94 for d4-homocysteine, and m/z 269.2?134.4 for d8-HCY. Results: The newly developed methodology demonstrated a sensitive method for the quantification of total HCY over a linear range of 2 ?mol/L–100 ?mol/L. Assay validation parameters such as intraday and interday assay precision, accuracy, and recovery were also within an acceptable range. Conclusion: In the present study, an in-house tandem mass spectrometric-based assay for the quantification of total HCY was developed which can be employed as an important strategy for the differential diagnosis of homocystinuria in neonates.